The Role of Strategic Intelligence in Organizational Success Analytical research in the colleges of the University of Fallujah - Hashem, Yaseen Rasheed; AI-Sheikhly, Abdul Razzaq Ibrahim (Journal of Economics and Administrative Sciences, 2021)
The current research aims to verify the role of strategic intelligence as an explanatory variable in organizational success as a respondent variable in the colleges of the University of Fallujah, the research community. (Dean, Associate Dean, Section Head, Division Officer, Unit Officer), The researcher used the questionnaire as the main tool to collect data that included (50) items, in addition to using personal interviews and field observations as aids in data collection. The researcher relied on statistical programs (SPSS V.25; Excel V (16) In the treatment and analysis of data through the use of the most appropriate statistical methods (arithmetic mean, standard deviation, difference coefficient, determination coefficient (R2), F test, simple linear regression, relative importance, Pearson correlation coefficient,) to test its hypotheses, the research has reached To a set of conclusions, the most important of which was that the top management in the colleges of the University of Fallujah use the dimensions of strategic intelligence represented by (foresight, thinking in systems, future vision, motivation, partnership) Grouped It is necessary to enhance organizational success, more than if these dimensions were used individually, and this indicates an interconnectedness and complementarity between these dimensions that has a greater impact on the collective style than if each dimension was used individually to achieve organizational success, this research proved the validity of the proposed hypotheses and the existence of Correlation and positive impact of strategic intelligence on organizational success, and based on the findings reached, a set of recommendations was developed, the most important of which was the need for higher management in the colleges of Fallujah University to pay attention to the process of motivating employees and efficient cadres, because the positive effects of the motivation process contribute to increasing efficiency and effectiveness Individuals working to achieve outstanding performance.